The Effect of Science LKPD Based Surrounding Environment on Learning Outcomes of Elementary School Students - Mega Krisdiana; Mafdurotul Goliah; Siti Malihah; Lukman Nulhakim; Suroso Mukti Leksono (Postgraduate, University of Mataram, 2023)
This study aims to find out how the influence of environment-based science worksheets on the learning outcomes of fifth grade elementary school students, especially in the subject of ecosystems and food chains. This study uses a quantitative method with a type of nonequivalent control group design that will be used in this study. The design to be used is a quasi-experimental design, namely the experimental class and the control class as research subjects. The experimental class is the class that will be studied using a treatment while the control class is the class that is studied using conventional methods or the way the teacher usually teaches. The sampling used in this study were 40 students with 20 students in the experimental class and 20 students in the control class. The collection of research data through tests. The hypothesis test that was carried out was the T test with a Sig (2-tailed) value of 0.717. This value is based on the basics of decision making, so the value is less than 0.05, so H0 is acceptable and shows an increase in student learning outcomes by using environment-based worksheets.